Oxidized and reduced Portuguese Variscan granites associated with W and Sn hydrothermal lode deposits: Magnetic susceptibility results [Granitos Variscos Portugueses oxidados e reduzidos e sua associação com mineralizações hidrotermais de W e Sn: Resultados de suscetibilidade magnética] - Sant'Ovaia, H (2013)
The central-northern region of Portugal mainland comprises an important W-Sn metallogenic province composed of various W, W-Sn, W-Mo and Sn hydrothermal lode deposits spatially related to Variscan granites. These granites are usually categorised into two main groups: the two-mica granites and biotite-bearing granites. As the granite series reflect redox states of their corresponding melts, the magnetite- and ilmenite-series represent oxidized- and reduced-type respectively. The mineralogical features and magnetic susceptibility (K) of the granites were examined in order to deduce the redox conditions of magma system. Despite of different petrographic and geochemical characteristics, K values in the majority of the granites studied vary from 20 to 300 × 10-6 SI units corresponding to reduced- or ilmenite-type granites. The oxidized-or magnetite-type granites are scarce and represented by some post tectonic biotite granites with K values ranging from 15 to 20 × 10-3 SI units. Major W and Sn ore deposits are related to two-mica and biotiterich granites both corresponding to reduced ilmenite-bearing granites; WMo lode deposits are in place related with biotite-rich granites belonging to oxidized series (i.e. magnetite or titanomagnetite-bearing granites). (c) 2013 LNEG - Laboratório Nacional de Geologia e Energia IP.